MORPHOGENESIS OF RAT’S THYROID GLAND IN PREWEANING PERIOD AFTER PRENATAL INFLUENCE OF STAPHYLOCOCCAL TOXOID - Fedosieieva О.V. (World of Medicine and Biology, 2020)
The results were obtained about morphogenesis of rat’s thyroid after intrauterine antigenic action of staphylococcal toxoid. Prenatal influence of staphylococcal toxoid led to the formation of a more pronounced structure of the parenchyma and stroma, but they showed signs of functional immaturity, which led to the presence of a morphological picture of hypothyroidism after birth (rats 1-7 days of postnatal ontogeny).With the beginning of the middle sucking period (7-21 days of life) there is a lymphoid infiltration in separate sites of a thyroid gland, processes of reorganization of the synthetic device and resorption of colloid, so functional "maturation" of already morphologically formed structures begins. Such abrupt changes in the thyroid gland of experimental animals are due to systemic prenatal antigenic influence on the body as a whole and is adaptive-compensatory in nature.